Using A*Algorithm and Google Maps API for Web-Based Path Optimisation Public Vehicles Routes in Medan City - Faridawaty; Arnita; Sri Dewi (Postgraduate, University of Mataram, 2024)
Public transport optimum route search is a problem to find a route between two points with the minimum number of weights. The research method that can be used to solve the problem of finding the optimum route is divided into two stages, namely first designing a model device using the A* algorithm and Google Maps API, second designing an android-based application. The purpose of this research is to develop an android-based system that can contain information on the optimum route of public transport in Medan City. The A* algorithm is a computer algorithm that uses distance estimation using the search for the closest path to reach the destination and has a heuristic function that is used as a basis for consideration to determine the choice of a number of alternatives to achieve the target effectively. The output of this research is the application of optimum route information for Medan city public transport based on android. The level of readiness of this research technology is of the Software type at the subsystem module validation status in a laboratory environment with indicators of integrated basic software components working together.